The EFFECT OF TARGET TRAINING ON PASSING ACCURACY OF U- 10 SSB LALAN FOOTBALL PLAYERS - adika hidayat saputra; Susanto, Ridho Bahtra; Susanto, Hadi Pery Fajri; Susanto, wilda welis (Jurnal IKEOR, 2025)
The inferior passing skill of the SSB Lalan FC U-10 football players is the issue in this study. Numerous elements contribute to this, including player motivation during training, coach skills, infrastructure and facilities, talent, and physical prowess. The purpose of this study is to determine if target training has an impact on SSB Lalan FC U-10 football players' passing accuracy. Quantitative research using experimental approaches is what this study is. The study's population consisted of 27 SSB Lalan FC U-10 football players. Purposive sampling is the method of sampling. Thus, 15 participants made up the study's sample. This study employed pre-tests (the beginning test) and post-tests (the final test) to gather data. This study's data analysis method makes use of the Normality and Homogeneity tests. According to the data processing, the pre-test and post-test normality test findings showed normal significant data at 0.100 and 0.709. Because it exceeds the 0.05 significance threshold, it is considered regularly distributed. As shown by the significant data findings of 0.055 in the pretest and post-test homogeneity test results, which are higher than the significance threshold of 0.05 and demonstrate a normal distribution. Thus, target training has an impact on the passing accuracy of SSB Lalan FC U-10 football players.